Peran Platfrom Digital Dalam Meningkatkan Interaksi Mahasiswa Antar Budaya di Era Globalisasi - Maulana, Ernawati; Widiyanarti, Tantry; Tsalitsa, Firly Amalia; Pratama, Seni Ledia; Mardhiyyah, Shofi; Ardika, Afla (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research discusses the role of digital platforms in enhancing cultural interaction among students in the era of globalization. Digital platforms such as social media and video conferencing applications have become important tools for students to exchange perspectives and cultures and collaborate virtually on international projects. collaborate virtually on international projects. This research technique with a descriptive approach to analyze data from various related literature. Analyze data from various related literatures. The results showed that the digital platform makes it easy for students from different cultural backgrounds to interact and learn from each other, increase cultural awareness and build intercultural tolerance, and build intercultural tolerance. Although digital platforms provide significant positive impact, challenges such as different communication styles and limited access to the internet and limited internet access are still an obstacle. This result shows that the digital platform not only enriches students' academy experience but also help them adapt and actively participate in a dynamic global society.